Supporting teachers to actively respond to bullying and to build positive relationships with their students: effects of the T-SUPPORT training - Finet, Chloë; Vandebosch, Heidi; Lubon, Anouck; Colpin, Hilde (Frontiers in Psychology, 2023)
Despite the central role that teachers can have in preventing and reducing bullying, they often feel insecure about how to deal with bullying. This study evaluated a short teacher training – called the Teachers SUPporting POsitive RelaTionships (T-SUPPORT) training – that aims to reduce bullying by supporting teachers in building positive teacher-student relationships and in actively dealing with bullying. The aim of the current study was to investigate whether the T-SUPPORT training resulted in higher quality teacher-student relationships, and more active and less passive responses to bullying incidents, and whether these improvements in turn resulted in lower levels of bullying victimization. In a Randomized Controlled Trial 10 Belgian primary schools were randomly assigned to an intervention or control condition. The Grades 4–6 teachers of the five schools in the intervention condition received the three-session school-based training; control teachers received no intervention. Grade 4–6 students (N = 964; 55 classrooms) in these schools completed questionnaires at pre- and post-test. In contrast to the hypotheses, results of the two-level linear mixed model analyses revealed no significant effect of the training on teacher-student relationship quality, teachers’ responses to bullying and bullying victimization. Yet, higher quality teacher-student relationships and more active teacher responses to bullying were significantly associated with less bullying victimization, whereas more passive responses were linked with more victimization. The latter findings are in line with theorizing and research on the role that teachers can play in reducing bullying.